A study on changes in phonetics in completely edentulous patients before and after rehabilitation with conventional and customized complete dentures - Niyogi, Soumadip; Bhattacharyya, Jayanta; Das, Samiran; Ghosh, Soumitra; Goel, Preeti; Chatterjee, Indranil (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: A realistic approach to the phonetic aspect in complete denture construction is most often subdued by various factors. The palatal rugae, an important landmark in speech orderliness, are frequently affected due to lack of proper texture on a complete denture. Establishing a correlation between customized palatal surfaces of complete dentures and speech improvement will help to ameliorate post insertion appointments of articulation deficiencies. Methods: Ten completely edentulous subjects of either sex with a mean age range of 50-70 years, fulfilling the inclusion criteria were included in this study. All the participants received three sets of dentures, followed by assessment of speech using photo articulation test, speech intelligibility and acoustic analysis in edentulous state and subsequently after insertion of conventional denture, denture with customized rugae, and denture with customized metallic base. Results: The data collected was subjected to statistical analysis using SPSS 24.0 version and GraphPad Prism version 5. The statistical analysis was carried using ANOVA and student t-test. On evaluating the error patterns, distortion was maximum followed by substitutions. These errors were maximum in edentulous state and decreased subsequently, with the least errors in customized rugae dentures. A statistically significant positive correlation (p<0.0001) was found. Conclusions: Apart from retention, stability and support, equal amount of emphasis has to be laid down on phonetical aspects to improve the overall psychological well-being and social upliftment for patients. The improvement in verbal proficiency for completely edentulous patients can be minimized considerably by customizing the palatal portions.